Perancangan sistem informasi berbasis web Pada Rumah Sakit Muhammadiyah Palembang - Muhammad Ihsan; Zulhipni Reno Saputra; Jimmie (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
There must be changes made to the system being used in order for it to be more effective and efficient if we are to increase the level of quality health care for the common people. Collection of data is crucial for the society as a whole's health care system. With the presence of information retrieval, certain information can be uncovered to support a process of public health care that can address any need for public health information. As the sole facility for providing healthcare services, Muhammadiah Palembang C type Hospital is located on Jl. A. Yani 13 in the nearby village of Ulu II in the city of Palembang. The system's performance in maintaining outpatient patient in Muhammadiyah Hospital Palembang is less than optimal because outpatient data is still collected manually. Many problems that people face in their homes include problems with input, data expansion, and the occurrence of duplicate patient files, making data processing less effective and efficient. This can hinder the course of reports and smoothness in terms of service to patients. Because of this issue, it is necessary to develop a software application that can assist sick households, specifically in the administration of raw land, as well as in the reduction of costs associated with raw land, as well as in providing convenience in obtaining relevant, accurate, and timely information.